Brazilian Buffalo Genetic Variability by Cross-Specific Microsatellite Set - Rogberg Muñoz, Andres (2011)
Buffaloes (Bubalus bubalis) were introduced to Brazil in 1895. As cross-species utility of microsatellites is one of the preferred marker choice criteria, 19 cattle microsatellites were tested to develop a multiplexed set of microsatellites and characterize Brazilian buffalo. Three panels were finally developed with eleven that succeed in amplify and were polymorphic (58%). The average number of alleles was 5.42, with an average observed and expected heterocigozity of 0.441 and 0.695, respectively. HWE tests results shows a disequilibrium (P < 0.05) in nine of the eleven loci, due to a significant increase of homozygotes in 8 of them. As it was expected, Brazilian Buffalo shows lower variability than Buffaloes from the domestication centres (China and India) but higher than the seriously selected European populations. Calculated overall exclusion power of the set in Brazilian buffalo allows its use in DNA based traceability. Furthermore, five highly informative tested microsatellites could be added to existing panels.